Reperceiving depression: how trait mindfulness enhances perceived support through improved doctor–patient relationships and stigma alleviation in depressed young adults - Zhu, Danhong; Yang, Yufeng; Wen, Jing; Liu, Chao (Frontiers in Psychology, 2025)
ObjectiveDepression, a prevalent mental health disorder among global youth, adversely impacts educational attainment, social functioning, and psychological wellbeing. Given the established protective function of perceived social support against depressive symptoms, this study investigates how trait mindfulness enhances such support through three mediating factors: therapeutic alliance perceptions, ruminative responses, and stigma internalization in clinically diagnosed adolescents.MethodsGuided by the Reperceiving Model of Mindfulness, this study examines the pathways connecting trait mindfulness, rumination, stigma, doctor–patient relationship perceptions, and perceived social support in adolescents with depression. Utilizing online convenience sampling, 569 participants (aged 14–30) meeting clinical depression criteria were recruited. Analytical procedures involved: Assessing measurement reliability and demographic variations using SPSS 26.0. Implementing structural equation modeling with Amos 26.0 to evaluate model fit, examine latent variable associations, and estimate standardized path coefficients.ResultsThe analysis demonstrated that trait mindfulness significantly enhanced perceived social support (β = 0.331, p < 0.001), with perceptions of the doctor–patient relationship partially mediating this relationship (indirect effect = 0.023, 95% CI [0.001–0.057]). Trait mindfulness also markedly reduced stigma (β = −0.375, p < 0.001), which subsequently diminished perceived social support (β = −0.177, p < 0.01). Stigma further mediated the mindfulness-social support linkage (indirect effect = 0.051, 95% CI [0.018–0.097]). In contrast, rumination showed no significant direct effect (β = −0.083, p =0.206) nor mediation capacity between trait mindfulness and social support (indirect effect = 0.040, 95% CI [−0.027 to 0.110]).ConclusionThis investigation establishes that trait mindfulness effectively augments perceived social support in depressed adolescents through dual pathways: enhancing doctor–patient relationship perceptions and mitigating stigma. Notably, rumination demonstrates no significant impact on social support acquisition in this clinical population. By delineating these mechanistic pathways, our findings highlight mindfulness-based interventions' therapeutic potential, proposing targeted training protocols to amplify social support networks for improved mental health outcomes in youth depression management.